Radial Artery Used as Conduit for Coronary Artery Bypass Grafting - Francesco Nappi; Aubin Nassif; Thibaut Schoell; Christophe Acar (Surgeries)
It was in 1989 that we first reported on the use of the radial artery (RA) as a secondary arterial graft for coronary artery bypass grafting (CABG). Nevertheless, discrepancies in clinical endpoints between the RA and alternative conduits have been reported in consecutive randomised trials. With over fifty years of accumulated practice in RA bypass grafting, we sought to identify the second-best option for CABG by reviewing the literature. A consistently successful second-best conduit for CABG has been demonstrated using the radial artery. Compared to saphenous vein grafts, the findings indicate improved outcomes and better patency results. Furthermore, it has been demonstrated to be a safe and effective conduit in the territory of the right coronary artery. The lack of available literature and the scarcity of similar case series restrict the application of the gastroepiploic artery. After five decades of utilisation, it can be unequivocally stated that the radial artery is the optimal conduit for coronary bypass surgery following the left internal thoracic artery to the left anterior descending artery.